Genome-Wide Identification and Expression Analysis of the Cation Diffusion Facilitator Gene Family in Turnip Under Diverse Metal Ion Stresses - Li, Xiong; Wu, Yuansheng; Li, Boqun; He, Wenqi; Yang, Yonghong; Yang, Yongping (Frontiers in Genetics, 2018)
The cation diffusion facilitator (CDF) family is one of the gene families involved in metal ion uptake and transport in plants, but the understanding of the definite roles and mechanisms of most CDF genes remain limited. In the present study, we identified 18 candidate CDF genes from the turnip genome and named them BrrMTP1.1–BrrMTP12. Then, we performed a comparative genomic analysis on the phylogenetic relationships, gene structures and chromosome distributions, conserved domains and motifs of turnip CDFs. The constructed phylogenetic tree indicated that the BrrMTPs were divided into seven groups (groups 1, 5, 6, 7, 8, 9 and 12) and formed three major clusters (Zn-CDFs, Fe/Zn-CDFs and Mn-CDFs). Moreover, the structural characteristics of the BrrMTP members in the same group were similar but varied among groups. To investigate the potential roles of BrrMTPs in turnip, we conducted an expression analysis on all BrrMTP genes under Mg, Zn, Cu, Mn, Fe, Co, Na and Cd stresses. Results showed that the expression levels of all BrrMTP members were induced by at least one metal ion, indicating that these genes may be related to the tolerance or transport of those metal ions. Basing on the roles of different metal ions for plants, we hypothesized that BrrMTP genes are possibly involved in heavy metal accumulation and tolerance to salt stress apart from their roles in the maintenance of mineral nutrient homeostasis in turnip. These findings are helpful to understand the roles of MTPs in plants and provide preliminary information for the study of the functions of BrrMTP genes.